Targeted immunotherapy for hair regrowth and regeneration - Toh, En Qi (2024)
Immunotherapy for skin conditions has a long and successful history. While the main strategy for treating inflammatory conditions is local or systemic immunosuppression, immunotherapy aims to stimulate parts or all of the immune system to bring about a therapeutic response. The immune system contains multiple, redundant avenues of checks and balances, and some immune cells have immunomodulatory or regulatory roles. These cells are targeted by immunotherapy in inflammatory skin conditions. Immunotherapy is effective in treating some hair loss disorders, supporting recent findings that the hair cycle is influenced by immune cells.